Analysis of stability and adaptability of QPM hybrids of maize growing in different Colombian agroecological zones - Ever Andrés vargas Escobar; Diosdado Baena García; José Ever Vargas Sánchez (Acta Agronómica)
Energy is maize´s biggest contribution for humans and animals. Scientist have been trying to increase its protein level since 1896, it wasn´t until the 60´s when the opaque gene O2 was discovered. In its recessive state, the gene causes the quality of the maize protein to increase, due to the growth of the Globulin protein and the reduction of Zein protein. Known as Quality Protein Maize (QPM), they can double the essential amino acids Lysine and Tryptophan´s percentages when compared with normal maize endosperm. In a commercial scenario, there is a need for high yielding genotypes adapted to different environments; it is also desirable to have a better protein quality. In the present study, 9 yellow endosperm QPM hybrids, developed by FENALCE from CIMMYT´s germoplasm and a normal commercial endosperm check were tested in 6 agro ecological zones: Wet Caribbean, Dry Caribbean, Orinoco, Valley of the Cauca River, Valley of the Magdalena River and the Coffee Growing Zone. A randomized complete block design was used in 17 environments and four repetitions. Variables concerning the plant and yield components were measured, but for this study the grain yield was the only taken. Additionally samples were taken to assess the content of Tryptophan. The stability and adaptability analysis was made using the Eberhart and Russell, Lin and Binns and AMMI models. The QPM hybrid that stood out for all the environments was QPM 303 and QPM 305 for unfavorable environments. Both retain their biochemical characteristics of protein quality and are stable in the evaluated environments according to the statistical models that were used.